ZBP-89, Sp1, and Nuclear Factor-κB Regulate Epithelial Neutrophil-activating Peptide-78 Gene Expression in Caco-2 Human Colonic Epithelial Cells - Keates, Andrew C.; Keates, Sarah; Kwon, John H.; Arseneau, Kristen O.; Law, David J.; Bai, Longchuan; Merchant, Juanita L.; Wang, Timothy C.; Kelly, Ciarán P. (The Journal of biological chemistry, 2001)
We reported previously that human colonic epithelial cells produce the C-X-C chemokine epithelial neutrophil-activating peptide-78 (ENA-78) and that its expression is up-regulated in ulcerative colitis. The aim of this study was to investigate the transcriptional regulation of ENA-78 gene expression in Caco-2 intestinal epithelial cells. Reporter gene transfection and electrophoretic mobility shift assay studies demonstrated that cooperation between two regions of the ENA-78 promoter were required for maximal gene expression in interleukin-1β-stimulated Caco-2 cells. Binding of activated p50/p65 nuclear factor-κB to nucleotides −82 to −91 was essential for interleukin-1β-dependent gene transcription, whereas binding of constitutively expressed zinc-requiring nuclear factors to nucleotides −125 to −134 (site A) was required for basal gene expression. Scanning mutagenesis of site A demonstrated overlapping binding elements at this locus. One site (CTCCCCC) bound Sp1 and Sp3, and overexpression of Sp1 (but not Sp3) up-regulated basal ENA-78 transcription. Another site (CCCCTCCCCC) was found to bind the zinc finger nuclear factor ZBP-89, and overexpression of this protein significantly repressed ENA-78 reporter gene activity. This study demonstrates that ENA-78 gene expression in Caco-2 intestinal epithelial cells is subject to complex regulation involving the coordinate binding of ZBP-89, Sp1, and nuclear factor-κB to the ENA-78 promoter.